Collaboration Framework for Digital Onboarding Program in Indonesian SMEs: An Exploration Research - Gunawan, Vania Pradipta; Trilaksono, Teddy; Prawiradipura, Herdy Jaya; Suhartanto, Eko; Rahayu, Sri; Dewantara, Made Handijaya (Department of Management, Faculty of Economics and Business, Brawijaya University, 2025)
This study investigates the effectiveness and challenges of Indonesia's digital onboarding program for Small and Medium Enterprises (SMEs) aimed at enhancing market access via digital marketplaces. Using a qualitative approach, data were collected through in-depth interviews and focus group discussions (FGDs) with 15 SME owners, representatives from four major e-commerce companies, and policymakers from the Ministry of Industry. Findings highlight significant gaps between planning and implementation, requiring tailored workshop materials, better coordination with marketplace enablers, and structured monitoring and evaluation (MONEV) systems. Success factors include appropriate marketplace selection, community engagement, and government support, while challenges involve monitoring difficulties, a lack of continuous mentorship, and digital literacy gaps. Managerial implications stress the importance of developing standardized training materials in collaboration with relevant associations, establishing clear learning outcomes and fostering continuous mentorship by successful SME champions. The findings of this study also contribute to policy makers and facilitators involved in this program by creating a framework for sustainable collaboration to ensure its long-term success and sustainability.